2009
DOI: 10.2478/v10012-008-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

On the modeling of car passenger ferryship design parameters with respect to selected sea-keeping qualities and additional resistance in waves

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The process of dimension reduction revealed the most relevant variables to predict aWRMS and MSI, including vessel journey duration, vessel speed, tidal range, current speed, significant wave height, and current direction. Some identified variables are typically present in the parameters used when exploring comfort or the incidence of motion sickness, including journey duration due to the negative relationship between duration and magnitudes of acceleration [36,37], the relationship between vessel speed and magnitudes of acceleration [38], and significant wave height and MSI [34,[39][40][41]. While other variables such as current speed, current direction, and tidal range are not typically present in parameters used in studies evaluating comfort and MSI, the dimensionality reduction process identified these parameters as relevant to the variance in predicting aWRMS and MSI.…”
Section: Welfare Modellingmentioning
confidence: 99%
“…The process of dimension reduction revealed the most relevant variables to predict aWRMS and MSI, including vessel journey duration, vessel speed, tidal range, current speed, significant wave height, and current direction. Some identified variables are typically present in the parameters used when exploring comfort or the incidence of motion sickness, including journey duration due to the negative relationship between duration and magnitudes of acceleration [36,37], the relationship between vessel speed and magnitudes of acceleration [38], and significant wave height and MSI [34,[39][40][41]. While other variables such as current speed, current direction, and tidal range are not typically present in parameters used in studies evaluating comfort and MSI, the dimensionality reduction process identified these parameters as relevant to the variance in predicting aWRMS and MSI.…”
Section: Welfare Modellingmentioning
confidence: 99%
“…The multi-criteria optimization was performed by using Pareto method. Such approach made it possible to present solutions in such a form as to allow decision makers (ship owners, designers) to select the most favorable solutions in each individual case [16].…”
Section: Introductionmentioning
confidence: 99%
“…: (7) where: (8) (9) (10) (11) where: Table 2 presents statistical parameters of the developed approximation with respect to the reference data, broken down by:…”
Section: Approximating the Added Wave Resistance Coefficientmentioning
confidence: 99%
“…They enable to calculate the added resistance from an irregular wave. In turn, the methods presented in [5,6,8] omit the effect of ship speed on the wave resistance and enable to calculate the resistance contribution only from a so-called statistical wave.…”
Section: )mentioning
confidence: 99%